Careers So You Want To Be An Expert Witness. - Boyell, R.L.
Roger L. Boyell says forensic engineering is a great job - if you can take the pressure.He's part of a growing cadre of engineers who are trading steady paychecks and corporate environments for the often solitary and occasionally adrenaline- inducing position of expert witness. It's their job to evaluate engineering systems, products, and devices and explain them in layman's terms in a courtroom.
Keywords: Devices evaluation; Engineering system evaluation; Expert witness; Forensic engineering career; Product evaluation